2013
DOI: 10.11634/233028791301431
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Determinants of Community Based Forest Management: Evidence from Alamata, Ethiopia

Abstract: In Ethiopia, community forest management (CFM) programme is adopted and implemented through participation of households in and around the forest for decades. The objective of this study was to assess the determinant factors of household participation level in community forest management. More specifically, it aimed to identify the effects of demographic, bio-physical and economic factors on households' level of participation. To achieve the objectives of the study, data were collected from 157 household respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 7 publications
6
13
0
1
Order By: Relevance
“…The household far from the forest did not benefit from the forest because it requires additional cost for transportation of grasses/other forest resources and information asymmetry on the different forest rehabilitation programs. The result is consistent with others studies conducted by Tadesse and Abay (2013) in Ethiopia and Musyoki et al (2013) in Kenya. They found a negative relationship between distances of a household's home from the forest and participation in forest management and rehabilitation practices due to information asymmetry and rare benefits obtained from the forest.…”
Section: Distance Of Forest From Home (Disfhom)supporting
confidence: 93%
See 3 more Smart Citations
“…The household far from the forest did not benefit from the forest because it requires additional cost for transportation of grasses/other forest resources and information asymmetry on the different forest rehabilitation programs. The result is consistent with others studies conducted by Tadesse and Abay (2013) in Ethiopia and Musyoki et al (2013) in Kenya. They found a negative relationship between distances of a household's home from the forest and participation in forest management and rehabilitation practices due to information asymmetry and rare benefits obtained from the forest.…”
Section: Distance Of Forest From Home (Disfhom)supporting
confidence: 93%
“…The prevailing shortage of land was initiating farmers to diversify forest-based incomes through managing the forest in a sustainable manner. The result is consistent with findings of Tadesse and Abay (2013), Eshetu et al (2014), Alemayehu et al (2015) in Ethiopia and Blay et al (2008) in Ghana and Musyoki et al (2013) in Kenya. They found that benefits obtained or expected from the forest such as timber and non-timber forest products serve as incentives for the households to engage more in forest management and rehabilitation practices.…”
Section: Benefit Derived or Expected From The Forest (Bendefst)supporting
confidence: 91%
See 2 more Smart Citations
“…Engida and Mengistu (2013) Meshack et al (2006) reported that Communitybased forest management (CBFM) could be a pathway to promoting a win-win situation in forest management strategies while still maintaining some amount of benefits received by communities from the forests and also guaranteeing a functioning ecosystem and maintenance of forest cover. Aabeyir et al (2011) suggested that achieving sustainable woodland management and controlling and ensuring fuel wood collection in a sustainable way is viewed as a major challenge to Ghana's traditional energy sector.…”
Section: Households Participation In Forest Management and Determinantsmentioning
confidence: 99%